(untitled) (Research, Society and Development, 2022)
Introduction: motivation is one of the greatest pillars for human work. Its role in the work of the nursing team is essential for the quality of the service. Objective: to understand the motivation of the nursing team. Methodology: a study described with a qualitative approach was conducted with nursing team professionals working in a hospital located in the north of Minas Gerais. Results: the results of the research indicate the working conditions, team interaction, valorization, training and salary as motivating factors. The professionals say they are unmotivated by the deficiency of the structuring factors of the service that hinder the work routine. On the other hand, it was evidenced during the interviews, what motivates the professionals of this nursing team, the act of caring, the liking of what it does. Conclusion: the essence of motivation is present in the group of professionals investigated, with health managers being responsible for intervening in hygienic factors that discourage this professional category.